2015
DOI: 10.1016/j.sbspro.2015.01.382
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Green Marketing Strategy on the Firm's Performance in Malaysia

Abstract: This is a conceptual paper to study the impacts of green marketing strategy on the Malaysian certified ISO 14001 Environmental Management System firms' performance. The paper aims at presenting the reviews of the literature on the green marketing and analyses the two factors that will influence the firms' performance. Despite the rising trend of consumers that willing to spend for a green product and the potential of green product, previous literature revealed that green marketing has encountered some challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(123 citation statements)
references
References 42 publications
7
110
0
6
Order By: Relevance
“…Ecological challenges today require managers to insert strategies that reduce pollution and preserve natural resources (Hasan and Ali, 2015). As a recent study in Greece has shown, several tourism-related ventures such as the development of ski resorts can contribute to the economic growth of a LFA but have a significantly negative environmental impact (Tsiaras, 2015) and, therefore, cannot be described as either sustainable or green.…”
Section: Resultsmentioning
confidence: 99%
“…Ecological challenges today require managers to insert strategies that reduce pollution and preserve natural resources (Hasan and Ali, 2015). As a recent study in Greece has shown, several tourism-related ventures such as the development of ski resorts can contribute to the economic growth of a LFA but have a significantly negative environmental impact (Tsiaras, 2015) and, therefore, cannot be described as either sustainable or green.…”
Section: Resultsmentioning
confidence: 99%
“…In 1995, Peattie described green marketing as "the management process for identifying, anticipating and satisfying the requirements of customers and society in a profitable and sustainable way" [21]. In addition, Hasan and Ali [22] noted that green promotion is one of the crucial factors that must be applied as a green marketing strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Green marketing can even be a panacea for struggling companies [58]. According to Hasan and Ali [22], green marketing strategy, including green innovation and green promotion, is a significant factor that affects to firms' profitability and customers' green consumption.…”
Section: Green Marketingmentioning
confidence: 99%
See 2 more Smart Citations